Development of TIMSS-Model Mathematics Problems with Banjar Cultural Ethnomathematics Context for Junior High School Students - Raudhah, Siti; Suryaningsih, Yuni; Noorbaiti, Rahmita (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
TIMSS results show that Indonesian students’ math skills remain low compared to other countries. Due to the limited number of participants selected through sampling, many students are unfamiliar with TIMSS-style questions. Therefore, it is necessary to develop TIMSS-modeled math problems to help more students practice and become familiar with the question format. This research aims to develop TIMSS-model math problems using Banjar cultural ethnomathematics that are valid, reliable, and practical. The study used a Research and Development (R&D) method with the ADDIE development model. The test subjects were 30 eighth-grade students from SMP Negeri 15 Banjarmasin. Instruments included validation sheets, student response questionnaires, and test scores. Two experts validated the product, resulting in a logical validity score of 3.78, categorized as valid. Based on student performance, the questions were empirically valid and reliable. The practicality score from the student questionnaire was 4.475, categorized as practical. This research successfully produced five descriptive math problems that meet the validity, reliability, and practicality criteria.